2017
DOI: 10.1016/j.neurobiolaging.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in the structural complexity of subcortical and ventricular structures

Abstract: It has been well established that the volume of several subcortical structures decreases in relation to age. Different metrics of cortical structure (e.g., volume, thickness, surface area, gyrification) have been shown to index distinct characteristics of inter-individual differences; thus, it is important to consider the relation of age to multiple structural measures. Here we compare age-related differences in subcortical and ventricular volume to those differences revealed with a measure of structural compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 83 publications
2
70
0
Order By: Relevance
“…The complexity of each structure was calculated using as the fractal dimensionality of the filled structure. Our work previously demonstrated that fractal dimensionality indexes age-related differences in cortical and subcortical structures better than extant measures (i.e., cortical thickness, cortical gyrification, subcortical volume), where older adults exhibit reductions in structural complexity relative to younger adults (Madan & Kensinger, 2016, 2017aMadan, in press). In fractal geometry, several approaches have been proposed to quantify the 'dimensionality' or complexity of a fractal; the approach here calculates the Minkowski-Bouligand or Hausdorff dimension (see Mandelbrot, 1967).…”
Section: Cortical Parcellationsmentioning
confidence: 87%
See 3 more Smart Citations
“…The complexity of each structure was calculated using as the fractal dimensionality of the filled structure. Our work previously demonstrated that fractal dimensionality indexes age-related differences in cortical and subcortical structures better than extant measures (i.e., cortical thickness, cortical gyrification, subcortical volume), where older adults exhibit reductions in structural complexity relative to younger adults (Madan & Kensinger, 2016, 2017aMadan, in press). In fractal geometry, several approaches have been proposed to quantify the 'dimensionality' or complexity of a fractal; the approach here calculates the Minkowski-Bouligand or Hausdorff dimension (see Mandelbrot, 1967).…”
Section: Cortical Parcellationsmentioning
confidence: 87%
“…Scan parameters were: TR=9.7 ms; TE=4.0 ms; flip angle=10°; voxel size=1.25×1×1 mm. This sample was previously used in Madan and Kensinger (2017a) and Madan (in press Mennes et al, 2013) and hosted on the the Neuroimaging Informatics Tools and Resources Clearinghouse (NITRC; Kennedy et al, 2016) (http://fcon_1000.projects.nitrc.org/indi/retro/dlbs.html). Participants were screened for neurological and psychiatric issues.…”
Section: Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one novel and exciting approach, recent studies by Madan and Kensinger 68, 69 found that the structural complexity of certain brain regions (including MTL and striatum) is a more sensitive measure of age-related differences than volume and cortical thickness. This approach leverages individual variability rather than controlling for its effects as a set of confounding variables.…”
Section: Individual Differences Are Informativementioning
confidence: 99%